Navigating Digital Learning in the Infrastructure Gap: Adaptive PjBL Strategy in the RPL Department of Vocational High Schools - Nazli Nahrowi; Aura Adhy Cahyaningsih; Imroatus Sholihah; Maghfira Ulil Azizah; Zaenal Abdul Rahmandani (Journal on Smart Learning Technologies, 2026)
Digital transformation in vocational education often encounters systemic barriers, particularly in resource-constrained settings where infrastructure gaps significantly contrast with industry demands. This study aims to analyze the navigation of Project-Based Learning (PjBL) strategies and technological adaptation in a Software Engineering (RPL) program facing extreme device scarcity. A qualitative descriptive case study was conducted at SMKN Takeran, Indonesia, involving one productive teacher and 36 students. Data were gathered through participatory observation, semi-structured interviews, and document analysis, subsequently processed using thematic analysis. The findings reveal that a device ratio of 1:12 does not halt digital transformation but instead triggers "adaptive collaboration" and "pedagogical resilience." Students developed organic resource-sharing mechanisms, while teachers innovated through self-developed digital media to compensate for laboratory limitations. However, a "competency paradox" emerges where local resilience creates a transition gap towards industry standards that prioritize individual technical autonomy. This research suggests that digital transformation in vocational settings should be redefined as a pedagogical-driven process rather than a hardware-centric one. It provides a strategic framework for policymakers to implement more inclusive digital initiatives in low-resource environments.